A Study on Bottom Friction Coefficient in the Bohai, Yellow, and East China Sea. (1st July 2014) - Wang, Daosheng; Liu, Qiang; Lv, Xianqing
Abstract : The adjoint tidal model based on the theory of inverse problem has been applied to investigate the effect of bottom friction coefficient (BFC) on the tidal simulation. Using different schemes of BFC containing the constant, different constant in different subdomain, depth-dependent form, and spatial distribution obtained from data assimilation, the M2 constituent in the Bohai, Yellow, and East China Sea (BYECS) is simulated by assimilating TOPEX/Poseidon altimeter data, respectively. The simulated result with spatially varying BFC obtained from data assimilation is better than others. Results and analysis of BFC in BYECS indicate that spatially varying BFC obtained from data assimilation is the best fitted one; meanwhile it could improve the accuracy in the simulation of M2 constituent. Through the analysis of the best fitted one, new empirical formulas of BFC in BYECS are developed with which the commendable simulated results of M2 constituent in BYECS are obtained.